ESTUDIO DEL APROVECHAMIENTO DEL Arapaima gigas (PAICHE), PARA LA ELABORACIÓN DE UN ALIMENTO FORTIFICADO, ADICIONANDO A SU FORMULACIÓN DISTINTAS GRASAS DE ORIGEN VEGETAL - Josselyn Jahaira, Bazurto Delgado (2023)
The purpose of this research is to study the use of Arapaima Gigas (Paiche) for the preparation of a hamburger-type meat product, where three vegetable fats were added to its formulation: OLEA EUROPEA (olive), Sesamum indicum (sesame), Elaeis Guineensis (palm), in addition to using the cuts (loin and belly) and adding two types of flours: Cicer Arietinum (chickpea) and Glycine max (soybean), for which bromatological analyses were carried out for each of the treatments and then the fatty acid profile of the best treatment was determined. The research was developed in the first place by elaborating the product, to indicate the differences in the bromatological analysis a factorial design AxBxC with 3 repetitions was used where the study factors were (Factor A: Types of cuts, Factor B: Types of flours Factor C: Types of oils). To determine the effects on the levels of the different treatments, the Tukey significance test was used (p < 0.05), the data obtained were analyzed within the statistical program "STATGRAPHICS" and "STATISTICA". As for the bromatological analyses carried out, it was determined that the belly cut had better characteristics in terms of protein, fat and fiber; as for the feasibility of the flours, it was observed that the chickpea flour had a better protein and fiber content, As for vegetable fats, sesame oil showed better protein and fiber content, while the best treatment for the analysis of fatty acid profile was presented in the interaction (loin cut + chickpea flour + palm oil), where saturated, unsaturated and polyunsaturated fatty acids were present.